Direct Connection between the RII Chain and the Nonautonomous Discrete Modified KdV Lattice - Maeda, K.; Tsujimoto, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
The spectral transformation technique for symmetric RII polynomials is developed. Use of this technique reveals that the nonautonomous discrete modified KdV (nd-mKdV) lattice is directly connected with the RII chain. Hankel determinant solutions to the semi-infinite nd-mKdV lattice are also presented.